Toward non-gas-permeable hBN film growth on smooth Fe surface. (5th May 2021) - Ko, Hayoung; Choi, Soo Ho; Kim, Jungmo; Kim, Yong In; Kim, Young-Hoon; Adofo, Laud Anim; Jung, Min-Hyoung; Kim, Young-Min; Jeong, Mun Seok; Kim, Ki Kang; Kim, Soo Min
Abstract: Flexible, transparent, and thermally stable gas barrier films are required to seal organic-based ultra-thin, flexible, and transparent electronic devices against moisture. Thermally stable, two-dimensional hexagonal boron nitride (hBN) is an ideal non-gas-permeable material with high transparency and flexibility. Nevertheless, the polycrystalline multilayer hBN (m-hBN) grown on a rough Fe foil by chemical vapor deposition is not sufficient for use as a gas barrier due to the non-uniformity and discontinuity of the film. Here, we report a novel method for synthesizing highly uniform and continuous m-hBN films on smooth Fe foil on a wafer scale via deposition of an amorphous Fe layer on a rough Fe foil. The amorphous Fe layer on a unary Fe foil is effectively recrystallized to become a smooth surface via post-thermal annealing treatment at 1100 °C. The smoothed surface allows for the uniform precipitation of B and N atoms to form a highly continuous m-hBN film, as confirmed by cross-sectional transmission electron microscopy. m-hBN/graphene heterostructure on polyethylene terephthalate further demonstrates the significant improvement of gas barrier performance; a water vapor transmission rate of 0.01 g m −2 day is achieved, which is seven times lower than the previously reported value, while retaining a high transparency of 96.4% at a wavelength of 550 nm.